Avaliação do papel de galectina-3 em camundongos experimentalmente infectados com Neospora caninum - Santana, Fernando William Moreira (2022)
Neospora caninum is a mandatory intracellular protozoan that belongs to the phylum Apicomplexa and is the causative of neosporosis, a disease of great medical-veterinary importance for causing neuromuscular diseases in dogs and abortions in cattle, generating great economic losses for dog owners and livestock companies, respectively. For these reasons, several studies have been made in the development of strategies for the prevention and treatment of this infection, including research related to innate immunity against this parasite. Among the receptors of innate immunity, the galectins, lectins proteins with affinity to β galactosides, recognize molecules present in parasites, stimulating the host’s immune response. In this context, our work aimed to determine the role of the galectin-3 in mice resistance during N. caninum infection. For this, we analyzed the morbidity and mortality rates from wild type (WT) and genetically depleted for Galectin-3 (Gal3-/- ) mice infected with tachyzoites, as well as histopathological changes, parasitism and antibody production in these animals in acute (7 days) and chronic (30 days) infection with N. caninum. We observed that the Gal3-/- mice had a less loss of body weight when compared to the WT group. However, there was no difference in cerebral parasitism between Gal3-/-and WT mice. In addition, Gal3-/- and WT mice showed similar inflammatory condition, with multiple inflammatory foci in the brain parenchyma. Moreover, we evaluated the influence of Galectin-3 in the production of IgG anti-N. caninum and we could notice that this molecule does not directly influence the production of IgG antibodies specific to N. caninum. Based on these data, we can conclude that there is no evidence that Galectin-3 participate in the immunological resistance process in mice during the infection by N. caninum protozoan.